PERAN DARI PERSEPSI PELAKU UMKM DAN PEMAHAMAN TEKNOLOGI INFORMASI TERHADAP PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH - Rahayu, Dewi; Pramesti Dewi, Hayuningtyas (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2025)
This study investigates factors that can influence the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), namely the perception of MSME actors and the understanding of information technology. Data were obtained from MSMEs fostered by Pondok Gede District, Bekasi City, and tested using partial least square analysis. The results showed that the perception of MSME actors and their understanding of information technology had a positive effect on the implementation of SAK EMKM.